PENGARUH PERSEPSI HARGA, KEPERCAYAAN MEREK, KUALITAS PELAYANAN dan LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Natasha Skin Clinic Center Gresik). - Melinda Desy Wahyuni (Jurnal Manajerial, 2019)
This study aims to determine how much the Influence of Price Perception, Brand Trust, Service Quality and Location on Consumer Purchasing Decisions of Natasha Skin Clinic Center. The population used in this study were Natasha Skin Clinic Center consumers with a total sample of 100 respondents using Non-Probability Sampling technique with a Quota Sampling approach, which is a technique to determine a sample of a population that has certain characteristics to the desired amount (quota) based on the results of the study found the regression equation as follows Y = 3,692 + 0,193X1 + 0,231X2 + 0,208X3 + 0,215X4 + e. Based on statistical data analysis, the indicators in this study are valid and reliable. The variable that has the greatest influence is the brand trust variable with a regression coefficient of 0.231, while the variable that has the smallest influence is the perception of price with a coefficient of 0.193. Hypothesis testing uses t test which shows that the four independent variables, namely price perception (X1), brand trust (X2), service quality (X3) and location (X4) which are examined, have proven to significantly influence the dependent variable, namely purchasing decision (Y). Then through the F test it can be seen that the price perception variable (X1), brand trust (X2), service quality (X3) and location (X4) together influence the purchasing decision (Y).